The Information Age: A new theological context (Vrhbosnensia: časopis za teološka i međureligijska pitanja, 2025)
The article explores how the digital revolution is transforming Christian theology, presenting new  challenges and opportunities. By analyzing the contextual nature of theology in the Information Age, the article examines the meaning of information and its implications for theological reflection, as well as the role of artificial intelligence in contemporary theological discourse. The Information Age has brought about radical changes in all aspects of human life, from communication and work to identity and the understanding of reality. These changes pose new questions and challenges for Christian theology, which must find ways to remain relevant and meaningful in a world increasingly shaped by technology. Within this framework, the Church seeks to provide guidelines that preserve human dignity and ensure the ethical application of new technologies. By addressing these topics, theology can serve as a guide, helping the faith community navigate the complex landscape of the Information Age, always emphasizing the central value of human dignity. Regarding the potential for evangelization in the Information Age, the article highlights how digital platforms and social media open new possibilities for spreading the Gospel, creating online communities, and enabling people worldwide to participate in religious life. The Church is called to adapt pastoral practices and utilize technological tools to respond to the needs of modern humanity, emphasizing ethical responsibility and the preservation of core Christian values.